PERJANJIAN JUAL BELI MELALUI MEDIA ELEKTRONIK (E-COMMERCE) BERDASARKAN KUH PERDATA DAN UU NOMOR 19 TAHUN 2016 (AKUN BUKALAPAK ‘WARUNG MAK KUNAPAH’) - Khamdanah Khamdanah; Arikha Saputra (Universitas Muhammadiyah Ponorogo, 2022)
PT. Bukalapak is a company that provides web portal services. Bukalapak provides a platform for online commerce called e-commerce. Warung Mak Kunapah is one of the sellers on the Bukalapak, the seller sells a variety of basic household items including rice, sugar, coffee and so on. If the buyer will make a purchase of goods sold by Warung Mak Kunapah, then the buyer is required to agree to the stages of the purchase on the purchase menu on the Bukalapak website. So that there is a sale and purchase transaction that can be referred to as a sale and purchase agreement with online media or using electronic media. Online buying and selling activities need to be known whether the agreement is legal according to the law. The goal is to find out that online buying and selling activities are legal according to the Civil Code and the ITE Law. And there is legal protection between the parties. In this research, the method used is normative juridical and analytical descriptive. Data collection with secondary data obtained from the literature. Data analysis was carried out using a qualitative descriptive method. The conclusion drawn is that the sale and purchase agreement using electronic media is in accordance with the Civil Code and the ITE Law, and there is legal protection for the parties in the electronic sale and purchase agreement at the Bukalapak E-commerce Company.